Vasectomy: knowledge, perception and acceptance by medical students in Latin America - Pierángely Prieto-Campos; Miguel Ángel Montiel-Alfonso; Humberto Alejandro Nati-Castillo; Alex Benjamín Araya-Morales; Beatriz Marqués de Brito; Florisel del Carmen Escudero; Ronny Richard Mera-Flores; Ideli Palazuelos-Guzman; Julio Rosales-Trujillo; Néstor Ricardo Botia-Silva (Revista de la Facultad de Medicina, 2022)
Introduction: Medical students play an important role in achieving sexual and reproductive health outcomes, including a greater participation of men in family planning.